Probe

By using the combination of Pt, Cu and Ni included in the material (A), the problem of consumption of the tip of the AgPdCu alloy probe due to the diffusion of solder components is solved, and the durability of the tip of the probe and the efficient operation of the inspection process are achieved.

CN119816739APending Publication Date: 2025-04-11YOKOWO CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380063454.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-07
Filing Date
2023-08-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

When using AgPdCu alloy probes, the diffusion of components in the solder leads to consumption of the probe tip, reducing the operation rate of the inspection process.

Method used

Material (A) is used to form a material (A) to suppress diffusion of solder components.

Benefits of technology

It effectively suppresses the diffusion of solder components to the probe, reduces the consumption of the probe tip, and improves the operation rate of the inspection process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119816739A_ABST
    Figure CN119816739A_ABST
Patent Text Reader

Abstract

The probe includes: 40% by mass or more and 95% by mass or less of Pt; 0.5% by mass or more and 50% by mass or less of Cu; and 3% by mass or more and 50% by mass or less of Ni.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to probes. Background Art

[0002] In order to inspect an inspection object such as an integrated circuit, the inspection object is sometimes electrically connected to the inspection substrate via a probe provided in a socket. The probe may sometimes contain an alloy of Ag, Pd, and Cu. Hereinafter, the alloy of Ag, Pd, and Cu is referred to as an AgPdCu alloy as required.

[0003] An example of an AgPdCu alloy is described in Patent Document 1. The AgPdCu alloy described in Patent Document 1 contains: 4% or more of Ag; about 35% to about 59% of Pd; and 16% or more and 50% or less of Cu.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: U.S. Patent No. 1935897 Summary of the invention

[0007] AgPdCu alloy is sometimes used for the material constituting the probe. However, when the tip of the probe containing AgPdCu alloy is repeatedly brought into contact with the solder of the inspection object to be electrically connected, there is a tendency for components such as Sn contained in the solder and components contained in the probe to diffuse with each other due to important reasons such as Joule heat. If the components contained in the solder diffuse, the tip of the probe will be consumed. Therefore, when using a probe containing AgPdCu alloy, the number of times the probe tip is cleaned and replaced becomes relatively large, and the operating rate of the inspection process will decrease.

[0008] One example of the purpose of the present invention is to suppress the diffusion of components contained in the solder to the probe. Other purposes of the present invention will become clear from the description of this specification.

[0009] One embodiment of the present invention is a probe comprising:

[0010] 40 mass % or more and 95 mass % or less of Pt;

[0011] 0.5 mass % to 50 mass % Cu; and

[0012] 3 mass % or more and 50 mass % or less of Ni.

[0013] According to the above aspect of the present invention, it is possible to suppress the diffusion of components included in the solder into the probe. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a cross-sectional view of the socket according to the embodiment.

[0015] Figure 2 It is a cross-sectional view of the socket according to the first modified example.

[0016] Figure 3 It is a cross-sectional view of a probe according to a second modified example.

[0017] Figure 4 It is a triangular graph showing the relationship between the mass ratio of Pt, the mass ratio of Cu, and the mass ratio of Ni contained in the test materials of Examples 1 to 14.

[0018] Figure 5 This is a diagram showing a scanning electron microscope (SEM) image of the tip of the contact portion of the first test pin before the electrical durability test.

[0019] Figure 6 This is a diagram showing a SEM image of the tip of the contact portion of the first test pin after the electrical durability test.

[0020] Figure 7 This is an enlarged SEM image of the tip of one of the sharp tips of the contact portion of the first test pin after the electrical durability test.

[0021] Figure 8 FIG. 5 is a diagram showing a SEM image of the tip of the contact portion of the second test pin before the electrical durability test.

[0022] Fig. 9 This is a diagram showing a SEM image of the tip of the contact portion of the second test pin after the electrical durability test.

[0023] Fig.10 This is an enlarged SEM image of the tip of one of the sharp tips of the contact portion of the second test pin after the electrical durability test.

[0024] Fig.11 This is a diagram showing a SEM image of the tip of the contact portion of the third test pin before the electrical durability test.

[0025] Fig.12 This is a diagram showing a SEM image of the tip of the contact portion of the third test pin after the electrical durability test.

[0026] Fig.13 This is an enlarged SEM image of the tip of one of the sharp points of the contact portion of the third test pin after the electrical durability test.

[0027] Fig.14 FIG. 4 is a diagram showing a SEM image of the tip of the contact portion of the fourth test pin before the electrical durability test.

[0028] Fig.15 This is a diagram showing a SEM image of the tip of the contact portion of the fourth test pin after the electrical durability test.

[0029] Fig.16 This is an enlarged SEM image of the tip of one of the sharp tips of the contact portion of the fourth test pin after the electrical durability test. DETAILED DESCRIPTION

[0030] Hereinafter, the embodiment and modification of the present invention will be described using the drawings. In all the drawings, the same components are denoted by the same reference numerals, and the description thereof will be appropriately omitted.

[0031] In this specification, unless otherwise specified, ordinal numbers such as "1st", "2nd", and "3rd" are used only to distinguish components with the same name and do not mean specific characteristics (such as order or importance) of the components.

[0032] Figure 1 It is a cross-sectional view of the socket 10 according to the embodiment.

[0033] Figure 1 In FIG. 1 , an arrow indicated by “+Z” indicates an upward direction in the vertical direction, and an arrow indicated by “−Z” indicates a downward direction in the vertical direction. Hereinafter, a direction perpendicular to the vertical direction will be referred to as a horizontal direction as necessary.

[0034] The socket 10 includes a probe 100 and an insulating support 200. The probe 100 is provided in a through hole formed in the insulating support 200. The probe 100 includes a first plug 110, a second plug 120, a tube 130, and a spring 140. Figure 1 1 shows a state where the inspection object 20 is inspected by the inspection substrate 30 using the probe 100. Specifically, Figure 1 The illustrated state is a state in which the solder balls 22 of the inspection target 20 and the pads 32 of the inspection substrate 30 are electrically connected via the probes 100 .

[0035] The tube 130 extends in the vertical direction. The spring 140 is located inside the tube 130. The probe 100 may not have the tube 130. The spring 140 is wound in a spiral shape around an imaginary axis passing through the center of the tube 130 in the vertical direction.

[0036] The first plug 110 is located on the upper end side of the spring 140. The first plug 110 is urged upward by the spring 140, that is, in a direction away from the second plug 120. When the inspection object 20 is inspected by the inspection substrate 30, the first plug 110 is connected to the inspection object 20 located above the probe 100. When the inspection object 20 is inspected by the inspection substrate 30, the top end, that is, the upper end, of the first plug 110 contacts the solder ball 22 of the inspection object 20. Figure 1In the example shown, the tip of the first plug 110 has a plurality of prongs arranged at equal intervals around an imaginary axis passing through the center of the first plug 110 in the vertical direction. The shape of the tip of the first plug 110 is not limited to Figure 1 Example shown.

[0037] The second plug 120 is located at the lower end side of the spring 140. The second plug 120 is urged downward by the spring 140, that is, in a direction away from the first plug 110. In a state where the inspection object 20 is inspected through the inspection substrate 30, the second plug 120 is connected to the inspection substrate 30 located below the probe 100. In a state where the inspection object 20 is inspected through the inspection substrate 30, the top end of the second plug 120, that is, the lower end, contacts the pad 32 of the inspection substrate 30. The top end of the second plug 120 is in a hemispherical shape. The shape of the top end of the second plug 120 is not limited to Figure 1 Example shown.

[0038] The first plug 110 includes a material (A). The material (A) includes: 40 mass % to 95 mass % of Pt; 0.5 mass % to 50 mass % of Cu; and 3 mass % to 50 mass % of Ni. For example, at least the surface of the first plug 110 is made of the material (A). In the example where at least the surface of the first plug 110 is made of the material (A), for example, the entire first plug 110 may also be made of the material (A). Alternatively, the material (A) may cover the surface of the first plug 110 by a process such as plating. In the case where the material (A) covers the surface of the first plug 110, the portion of the first plug 110 covered by the material (A) may also be made of a material different from the material (A). In addition, for example, at least the portion of the first plug 110 that contacts the solder ball 22 may also be made of the material (A). In the example where at least the portion of the first plug 110 in contact with the solder ball 22 is made of the material (A), the material (A) may be processed by plating or the like to cover only the surface of the portion of the first plug 110 in contact with the solder ball 22 .

[0039] The lower limit of the mass ratio of Pt contained in the material (A) is determined from the viewpoint of the corrosion resistance of the material (A). If the mass ratio of Pt contained in the material (A) is less than 40 mass %, the corrosion resistance of the material (A) is insufficient, and thus the mass ratio of Pt contained in the material (A) can be set to 40 mass % or more. The mass ratio of Pt contained in the material (A) can also be set to 45 mass % or more or 50 mass % or more.

[0040] The upper limit of the mass ratio of Pt contained in the material (A) is determined from the viewpoint of the hardness of the material (A) hardened by strong working. If the mass ratio of Pt contained in the material (A) exceeds 95 mass%, the hardness of the material (A) hardened by strong working may not reach 300 HV, and the hardness required for the first plug 110 may not be reached. Therefore, the mass ratio of Pt contained in the material (A) can be set to 95 mass% or less. The mass ratio of Pt contained in the material (A) can also be set to 90 mass% or less or 83 mass% or less.

[0041] The mass ratio of Pt contained in the material (A) can be, for example, 45 mass % to 90 mass %, or the mass ratio of Pt contained in the material (A) can be, for example, 50 mass % to 83 mass %.

[0042] The lower limit of the mass ratio of Cu contained in the material (A) is determined from the viewpoint of the hardness of the material (A). By adding Cu to Pt, the hardness of the material (A) can be improved while the processability of the material (A) is well maintained. However, if the mass ratio of Cu contained in the material (A) is less than 0.5 mass %, the hardness of the material (A) is insufficient, and thus, the mass ratio of Cu contained in the material (A) can be set to more than 0.5 mass %. The mass ratio of Cu contained in the material (A) can also be set to more than 2 mass % or more than 5 mass %. In addition, the mass ratio of Cu contained in the material (A) can also be set to more than 9 mass %.

[0043] The upper limit of the mass ratio of Cu contained in the material (A) is determined from the viewpoint of the corrosion resistance of the material (A). If the mass ratio of Cu contained in the material (A) exceeds 50 mass %, the corrosion resistance of the material (A) is insufficient, and thus, the mass ratio of Cu contained in the material (A) can be set to 50 mass % or less. The mass ratio of Cu contained in the material (A) can also be set to 40 mass % or less or 30 mass %.

[0044] The mass ratio of Cu contained in the material (A) can be, for example, 2 mass % to 40 mass %, or the mass ratio of Cu contained in the material (A) can be, for example, 5 mass % to 30 mass %.

[0045] The lower limit of the mass ratio of Ni contained in the material (A) is determined from the viewpoint of the hardness of the material (A) to be work-hardened. By making the material (A) contain Ni, the inhibition of diffusion between the components contained in the material (A) and the components contained in the solder such as the solder ball 22 will not be reduced, and the hardness of the material (A) to be work-hardened can be improved. However, if the mass ratio of Ni contained in the material (A) is less than 3% by mass, there is a situation where the hardness of the material (A) to be work-hardened is insufficient, and thus, the mass ratio of Ni contained in the material (A) can be set to 3% or more. The mass ratio of Ni contained in the material (A) can also be set to 5% or more or 10% by mass.

[0046] The upper limit of the mass ratio of Ni contained in the material (A) is determined, for example, from the viewpoint of plastic processing such as cold rolling and wire drawing of the material (A). If the mass ratio of Ni contained in the material (A) exceeds 50 mass %, there is a situation where plastic processing such as cold rolling and wire drawing of the material (A) becomes difficult, and thus, the mass ratio of Ni contained in the material (A) can be set to 50 mass % or less. The mass ratio of Ni contained in the material (A) can also be set to 40 mass % or less or 35 mass % or less, for example.

[0047] The mass ratio of Ni contained in the material (A) can be, for example, 5 mass % to 40 mass %, or the mass ratio of Ni contained in the material (A) can be, for example, 10 mass % to 35 mass %.

[0048] In the embodiment, compared with the case where the first plug 110 includes the AgPdCu alloy, it is possible to suppress the diffusion of the components included in the solder ball 22 into the first plug 110 at the interface between the tip of the first plug 110 and the surface of the solder ball 22. In addition, in the embodiment, compared with the case where the first plug 110 includes the AgPdCu alloy, it is possible to suppress the diffusion of the components included in the solder ball 22 into the first plug 110, thereby suppressing the consumption of the tip of the first plug 110.

[0049] When material (A) is used, the diffusion of components contained in the solder into material (A) is suppressed compared to the case where AgPdCu alloy is used, and the reason is presumed to be as follows. That is, when material (A) contacts the solder, a dense film containing metal compounds such as Sn-Ni is formed at the interface between material (A) and the solder due to Ni contained in material (A). When the metal compound exists at the interface between material (A) and the solder, the diffusion of the components contained in the material (A) and the solder is suppressed by the metal compound compared to the case where the metal compound does not exist at the interface between material (A) and the solder. However, when AgPdCu alloy is used, it is difficult to form the above-mentioned metal compound. Therefore, in the embodiment, compared to the case where the first plug 110 contains AgPdCu alloy, it is possible to suppress the diffusion of components contained in the solder ball 22 into the first plug 110 between the top of the first plug 110 and the solder ball 22.

[0050] For material (A), there is no requirement for a hardness equivalent to that of the existing AgPdCu alloy. However, as the number of inspections increases, the contact surface of the first plug 110 may sometimes mechanically collapse, so material (A) is preferably harder. For example, the first plug 110 can be used at a hardness of more than 200 HV. The hardness of material (A) is sometimes required to be more than 250 HV, preferably 300 HV. In addition, the hardness of material (A) may also be a hardness increased by work hardening.

[0051] A relatively low specific resistance may be required for the material (A). For example, the specific resistance of the material (A) can be set to 90 μΩ·cm or less. By reducing the specific resistance of the material (A), the Joule heat generated from the material (A) can be suppressed during inspection using the probe 100 .

[0052] Figure 2 1 is a cross-sectional view of a socket 10A according to a first modification. The socket 10A according to this modification is the same as the probe 100 according to the embodiment except for the following points.

[0053] An extension portion 112A extending downward from the first plug 110A is provided at the lower end of the first plug 110A. The first plug 110A and the extension portion 112A are integrated. Therefore, both the first plug 110A and the extension portion 112A contain the material (A). A front end 114A is provided at the lower end of the extension portion 112A. The front end 114A may or may not contain the material (A).

[0054] A base end 122A is provided at the upper end of the second plug 120A. A hole 124A is formed on the upper surface of the base end 122A, which opens toward the upper side of the base end 122A. A locking portion 126A is provided at a portion of the inner wall that defines the hole 124A in the base end 122A. The horizontal diameter of the locking portion 126A of the hole 124A is narrower than the horizontal diameter of the portion located below the locking portion 126A of the hole 124A. The front end head 114A extends downwardly compared to the locking portion 126A of the hole 124A. In addition, the front end head 114A can move in the vertical direction below the locking portion 126A of the hole 124A. The horizontal diameter of the front end head 114A is larger than the horizontal diameter of the locking portion 126A of the hole 124A. Therefore, the locking portion 126A prevents the front end head 114A from escaping toward the upper side of the hole 124A.

[0055] The probe 100A of this modified example does not have a tube corresponding to the tube 130 of the probe 100 of the embodiment. The spring 140A is located between the lower end of the first plug 110A and the upper end of the base end 122A. In addition, the spring 140A is wound around the extension 112A in a spiral shape. The first plug 110A, the extension 112A, and the front end 114A are urged upward by the spring 140A. The second plug 120A and the base end 122A are urged downward by the spring 140A.

[0056] Figure 3 2 is a cross-sectional view of a probe 100B according to a second modification. The probe 100B according to this modification is the same as the probe 100 according to the embodiment except for the following points.

[0057] Figure 3 In the example shown, the first plug 110B and the tube 130B are integrated. Therefore, both the first plug 110B and the tube 130B contain the material (A). In addition, the first plug 110B and the tube 130B are urged upward by the spring 140B, that is, in a direction away from the second plug 120B. The second plug 120B is urged downward by the spring 140B, that is, in a direction away from the first plug 110B.

[0058] As mentioned above, although embodiment and modification of this invention are demonstrated referring drawings, these are illustrations of this invention, and various structures other than what was described above can also be adopted.

[0059] Example

[0060] One embodiment of the present invention will be described based on examples and comparative examples. The present invention is not limited to the following examples.

[0061] Table 1 is a table showing the composition contained in the test materials of Examples 1 to 14 and Comparative Examples 1 to 2. In Examples 1 to 14 and Comparative Example 2 in Table 1, the expression "αPtβCuγNi" means that the test material contains α mass % Pt, β mass % Cu, and γ mass % Ni. In Comparative Example 1, the expression "24.5Ag45Pd25Cu0.5In" means that the test material contains 24.5 mass % Ag, 45 mass % Pd, 25 mass % Cu, and 0.5 mass % In.

[0062]

Table 1

[0063]

[0064]

[0065] The test materials of Examples 1 to 14 and Comparative Examples 1 and 2 were prepared as follows.

[0066] In Example 1, as shown in Table 1, 95 mass % of Pt, 2 mass % of Cu and 3 mass % of Ni were blended to obtain a coordination compound. In Examples 2 to 14 and Comparative Example 2, Pt, Cu and Ni were blended so as to have the compositions of Examples 2 to 14 and Comparative Example 2 shown in Table 1, respectively, to obtain a coordination compound. In Comparative Example 1, Ag, Pd, Cu and In were blended so as to have the composition of Comparative Example 1 shown in Table 1, to obtain a coordination compound.

[0067] Then, regarding Examples 1 to 14 and Comparative Examples 1 and 2, the above-mentioned coordination compound was dissolved by arc welding in an argon atmosphere to produce alloy ingots.

[0068] Then, for Examples 1 to 14 and Comparative Examples 1 to 2, the above-mentioned alloy ingots were rolled and heat treated repeatedly, thereby producing plates with a rolling ratio of 80%. The rolling ratio RR is determined by the following formula (1), with the thickness of the alloy ingot before rolling being t1 and the thickness of the alloy ingot after rolling being t2.

[0069] RR={(t1-t2) / t1}×100 (1)

[0070] With respect to Examples 1 to 14 and Comparative Example 1, a plate having a rolling reduction of 80% could be produced. With respect to Comparative Example 2, a plate having a rolling reduction of 80% could not be produced. With respect to Comparative Example 2, the measurement described using Table 2 described later could not be performed.

[0071] Table 2 is a table showing the measurement results of the specific resistance of the test material (unit: μΩ·cm), the processed material hardness of the test material (unit: HV), and the thickness of the diffusion layer between the test material and the solder (unit: μm) for Examples 1 to 14 and Comparative Example 1.

[0072]

Table 2

[0073]

[0074] Regarding Examples 1 to 20 and Comparative Example 1, the resistance R of each test material was measured at room temperature, and the specific resistance ρ was calculated according to the following formula (2) to measure the specific resistance of the test material.

[0075] ρ=RS / l (2)

[0076] Here, l is the measured length in the direction of current flow in the test material, and S is the cross-sectional area perpendicular to the direction of current flow in the test material. In the measurement of specific resistance, a plate with a rolling ratio of 90% was used as the test material.

[0077] As shown in Table 2, the specific resistance is less than 90 μΩ·cm in Examples 1 to 14. Therefore, it can be said that the specific resistance required for the probe can be obtained in Examples 1 to 14.

[0078] Regarding Examples 1 to 14 and Comparative Example 1, the center of the cross section of each test material was held at a load of 200 gf for 10 seconds using a Vickers hardness tester to measure the processed material hardness of the test material.

[0079] As shown in Table 2, in Examples 1 to 14, the hardness of the processed material is 300 HV or more. Therefore, it can be said that in Examples 1 to 14, the hardness required for the probe can be obtained.

[0080] For each of Examples 1 to 14 and Comparative Example 1, the thickness of the diffusion layer between the test material and the solder was measured as follows. First, a Sn-Bi solder was placed on a test material of 10 mm × 10 mm × 0.5 mm in thickness. Then, the test material and the Sn-Bi solder were heat treated at 250°C for one hour in a N2 atmosphere while the Sn-Bi solder was placed on the test material, so that the solder melted on the test material. Then, the test material was embedded in a resin, and the cross-section containing both the test material and the solder was exposed. Then, the interface between the test material and the solder was subjected to a radiographic analysis in a direction perpendicular to the interface using EPMA (Electron Probe MicroAnalyzer). In Examples 1 to 14, the diffusion layer was set as a layer in which both Sn diffused from the solder and Pt, the main element diffused from the test material, were present in the radiographic analysis. In Comparative Example 1, the diffusion layer was set as a layer in which both Sn diffused from the solder and Pd, the main element diffused from the test material, were present in the radiographic analysis.

[0081] As shown in Table 2, in Comparative Example 1, the thickness of the diffusion layer was 600 μm or more. In Examples 1 to 14, the thickness of the diffusion layer was less than 100 μm. Therefore, in Examples 1 to 14, it can be said that the diffusion of the components contained in the solder into the test material can be suppressed compared with Comparative Example 1.

[0082] The results shown in Table 2 indicate that, in the test materials of Examples 1 to 14, compared with the test material of Comparative Example 1, the specific resistance and workpiece hardness required for the probe can be achieved while suppressing the diffusion of components contained in the solder into the test material.

[0083] Figure 4 It is a triangular graph showing the relationship between the mass ratio of Pt, the mass ratio of Cu, and the mass ratio of Ni contained in the test materials of Examples 1 to 14.

[0084] The side from the lower right vertex to the upper central vertex of the triangular graph represents the mass ratio (unit: mass %) of Pt contained in the test material. The side from the upper central vertex to the lower left vertex of the triangular graph represents the mass ratio (unit: mass %) of Cu contained in the test material. The side from the lower left vertex to the lower right vertex of the triangular graph represents the mass ratio (unit: mass %) of Ni contained in the test material.

[0085] Figure 4The shaded area in the triangular graph indicates that the mass ratio of Pt is 40 mass % to 95 mass %, the mass ratio of Cu is 0.5 mass % to 50 mass %, and the mass ratio of Ni is 3 mass % to 50 mass %. The plotted points of Examples 1 to 14 are located within the shaded area. According to the tendency of the plotted points of Examples 1 to 14, it can be said that at any point within the shaded area, compared with the case where the test material is an AgPdCu alloy, the diffusion of the components contained in the solder to the test material can be suppressed.

[0086] Figure 5 This is a diagram showing a scanning electron microscope (SEM) image of the tip of the contact portion of the first test pin before the electrical durability test. Figure 6 This is a diagram showing a SEM image of the tip of the contact portion of the first test pin after the electrical durability test. Figure 7 This is an enlarged SEM image of the tip of one of the sharp tips of the contact portion of the first test pin after the electrical durability test.

[0087] The first test pin contained the test material of Example 2. Figure 5 as well as Figure 6 As shown, the tip of the contact portion of the first test pin has four prongs arranged at equal intervals around the central axis of the test pin.

[0088] In the electrical durability test, a flying probe test was used to bring the tip of the contact portion of the first test pin into contact with Sn-40Bi solder at a temperature of 125° C. and to flow a current of 1 A for 20 ms. This operation was repeated 10,000 times.

[0089] The length of the first test pin before the electrical durability test was compared with the length of the first test pin after the electrical durability test, and the consumption amount of the first test pin was calculated. The consumption amount of the first test pin was 0 μm.

[0090] Figure 8 FIG. 5 is a diagram showing a SEM image of the tip of the contact portion of the second test pin before the electrical durability test. Fig. 9 This is a diagram showing a SEM image of the tip of the contact portion of the second test pin after the electrical durability test. Fig.10 This is an enlarged SEM image of the tip of one of the sharp tips of the contact portion of the second test pin after the electrical durability test.

[0091] The second test pin was the same as the first test pin except that the second test pin contained the test material of Example 3. The conditions of the electrical durability test in the second test pin were the same as those in the first test pin.

[0092] The length of the second test pin before the electrical durability test and the length of the second test pin after the electrical durability test were compared to calculate the amount of consumption of the second test pin. The amount of consumption of the second test pin was 0 μm.

[0093] Fig.11 This is a diagram showing a SEM image of the tip of the contact portion of the third test pin before the electrical durability test. Fig.12 This is a diagram showing a SEM image of the tip of the contact portion of the third test pin after the electrical durability test. Fig.13 This is an enlarged SEM image of the tip of one of the sharp points of the contact portion of the third test pin after the electrical durability test.

[0094] The third test pin was the same as the first test pin except that the third test pin contained the test material of Example 8. The conditions of the electrical durability test in the third test pin were the same as those in the first test pin.

[0095] The length of the third test pin before the electrical durability test and the length of the third test pin after the electrical durability test were compared to calculate the consumption of the third test pin. The consumption of the third test pin was 1 μm.

[0096] Fig.14 FIG. 4 is a diagram showing a SEM image of the tip of the contact portion of the fourth test pin before the electrical durability test. Fig.15 This is a diagram showing a SEM image of the tip of the contact portion of the fourth test pin after the electrical durability test. Fig.16 This is an enlarged SEM image of the tip of one of the sharp tips of the contact portion of the fourth test pin after the electrical durability test.

[0097] The fourth test pin was the same as the first test pin except that the fourth test pin contained the test material of Comparative Example 1. The conditions of the electrical durability test in the fourth test pin were the same as those in the first test pin.

[0098] The length of the fourth test pin before the electrical durability test and the length of the fourth test pin after the electrical durability test were compared to calculate the amount of wear of the fourth test pin. The amount of wear of the fourth test pin was 4 μm.

[0099] Based on the results of consumption of the first test pin, the second test pin, the third test pin and the fourth test pin, it can be said that when the test pin contains 40 mass % to 95 mass % of Pt, 0.5 mass % to 50 mass % of Cu and 3 mass % to 50 mass % of Ni, the consumption of the top end of the test pin can be suppressed compared to the case where the test pin contains AgPdCu alloy.

[0100] According to the present specification, the following probes are provided.

[0101] (Method 1)

[0102] In aspect 1, the probe includes: 40 mass % to 95 mass % of Pt; 0.5 mass % to 50 mass % of Cu; and 3 mass % to 50 mass % of Ni.

[0103] According to the above aspect, compared with the AgPdCu alloy, it is possible to suppress the diffusion of components included in the solder into the probe at the interface between the probe and the solder.

[0104] This application claims priority based on Japanese patent application No. 2022-141968, filed on September 7, 2022, the disclosure of which is incorporated herein in its entirety.

[0105] Description of Reference Numerals

[0106] 10, 10A socket, 20 inspection object, 22 solder ball, 30 inspection substrate, 32 pad, 100, 100A, 100B probe, 110, 110A, 110B first plug, 112A extension portion, 114A front end head, 120, 120A, 120B second plug, 122A base end portion, 124A hole, 126A locking portion, 130, 130B tube, 140, 140A, 140B spring, 200 insulating support body.

Claims

1. A probe, wherein: include: 40 mass % or more and 95 mass % or less of Pt; 0.5 mass % to 50 mass % of Cu; and 3 mass % or more and 50 mass % or less of Ni.

Citation Information

Patent Citations

  • Walking support system, walking support method, and walking support program

    JP2022141968A

  • Precious metal alloy

    US1935897A